ANALISIS PENGARUH DESAIN PRODUK DAN PROMOSI TERHADAP KEMANTAPAN KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH CITRA MEREK (Studi pada Customer Distro Jolly Roger Semarang) - Rachman, Bayu Januar; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2015)
This research is motivated sales decrease distributions Jolly Roger. The sales decline shows a decrease in consumer purchasing decisions on product distributions Jolly Roger that can be formulated in this study that how consumers make purchasing decisions of products Jolly Roger in the middle of the phenomenon of increasingly fierce competition based on product design, promotion, brand image. The purpose of this study was to analyze the influence of product design and promotion of the brand image and analyze the influence of product design, promotion, and brand image to the stability of the product purchase decisions Jolly Roger.The sample in this study amounted to 100 respondents. Isntrumen questionnaire used as data collectors. Testing the validity and reliability of the above indicators and the concept of the variable indicates the validity and reliability that qualify as instruments. Multiple linear regression analysis is used to determine the influence of these variables on product design and promotion of the brand image and influence product design, promotion, and brand image to the stability of the purchasing decision.The test results by using multiple regression test showed that the design of the product proved significant positive effect on brand image, promotion proved significant positive effect on brand image, product design proved significant positive effect on the stability of the purchase decision, promotion proved significant positive effect on the stability of the purchase decision, and brand image proved significant positive effect on the stability of the purchase decision.